INFLUENCE OF MILLING TIME ON GROWTH MORPHOLOGY AND MECHANICAL PROPERTIES OF ALUMINUM-SILICON-CARBIDE COMPOSITES (Jurnal Teknologi (Sciences & Engineering), 2015)
Achieving improved mechanical properties of aluminum (Al) in the composite structures by mixing ceramics is ever-demanding for sundry applications. We synthesize aluminum-silicon-carbide composites via ball milling of aluminum which is reinforced with 5% of the silicon carbide (SiC) powders having particles size of 20 µm. Microstructures of powdered composite is characterized via XRD, EDX, and FESEM measurements. These mixtures are grinded at the speed of 200 rpm in a planetary ball mill for 0, 40, 80, and 120 minutes using zirconium balls as milling media. The ratio of the ball to powder is selected to be 10:1. At room temperature and pressure of 10 ton the mixed powders are die-pressed in a cylindrical stainless steel mold having internal diameter of 12.7 mm. The impact of milling time on the growth morphology (microstructures) and mechanical properties of the prepared Al–SiC (5 wt %) composite are scrutinized. The method mechanical alloying (MA) is comprised of milling, cold pressing, and sintering. The increase in milling time is demonstrated to enhance the hardness of the composites. Furthermore, the highest hardness and superior strength is achieved for 80 minutes of milling. Both the hardness and strength of such composites are decreased beyond this milling time. The excellent features of the results suggest that Al–SiC (5 wt%) composite with the present composition may be potential to fortify the structural network in terms of strength and stiffness.